Strategi Komunikasi Pada Sub bidang Pengelolaan Informasi Komunikasi Publik (PIKP) Di Dinas Komunikasi Dan Informatika Dalam Penyebaran Informasi Kepada Masyarakat Kabupaten Sijunjung - Yusuf Maiyondra; Dion Eriend (CV. ITTC INDONESIA, 2025)
This study aims to analyze the communication strategy implemented by the Public Communication Information Management Sub-sector at the Sijunjung Regency Communication and Informatics Office in disseminating information to the public. Communication strategy is an important element in increasing transparency and effectiveness in delivering public information. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. Informants in this study consisted of the head of the office, the head of the public communication information management division, and the community as supporting informants. The results of the study show that the communication strategy implemented includes the use of digital and social media, collaboration with mass media, direct communication with the community, and the use of digital technology and applications. Although the strategy implemented is quite effective, there are several obstacles, such as limited expertise in managing digital systems, limited information technology infrastructure in several areas, and dependence on digital platforms that have not reached all levels of society. To overcome these obstacles, the Sijunjung Regency Communication and Informatics Office developed a village communication network and utilized conventional media to expand the reach of information. With a good communication strategy, it is hoped that public information services in Sijunjung Regency can be increasingly optimal and able to meet the community's needs for accurate, fast, and transparent information.